2016
DOI: 10.3926/ic.727
|View full text |Cite
|
Sign up to set email alerts
|

Marketing assets: Relating brand equity and customer equity

Abstract: Purpose: Brand equity and customer equity are inextricably linked. Some authors propose that marketing activities build these intangible assets simultaneously. In contrast, others suggest that brand equity is an antecedent of customer equity. In this research, we aim to shed light about the relationship between brand equity and customer equity, by empirically testing these two alternative explanations. Design/methodology:We propose four research models that reflect these two alternatives explanations regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 80 publications
1
3
0
1
Order By: Relevance
“…Hypothesis 2 establishes a direct and positive relationship between brand equity and market value. The results have confirmed this relationship in both periods under study, which confirms what was previously concluded by authors such as Lo (2012) or Romero and Yagüe (2016) who also observed this relationship. In addition, in the case of this work, it should be noted that this relationship was verified for a type of companies with particular characteristics, such as multinational companies, without focusing on a specific sector.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hypothesis 2 establishes a direct and positive relationship between brand equity and market value. The results have confirmed this relationship in both periods under study, which confirms what was previously concluded by authors such as Lo (2012) or Romero and Yagüe (2016) who also observed this relationship. In addition, in the case of this work, it should be noted that this relationship was verified for a type of companies with particular characteristics, such as multinational companies, without focusing on a specific sector.…”
Section: Discussionsupporting
confidence: 92%
“…Brand equity is considered one of the most important intangible assets that exists when it comes to business management (Romero & Yagüe, 2016), as it is positively related to the financial performance of organizations and their survival in the market. "Brands are one of the most valuable assets and their management a key activity in any company" (Ludvík et al, 2018, p. 224).…”
Section: Brand Equity and Market Valuementioning
confidence: 99%
“…Ekuitas merek berbasis pelanggan terjadi ketika pelanggan akrab dengan merek dan memiliki beberapa asosiasi yang menguntungkan, kuat, dan unik dalam ingatan mereka (Keller dalam Sherman, et.al 2015). Ini menunjukkan bahwa portofolio merek dan pelanggan adalah aset pemasaran tidak berwujud yang membantu perusahaan menghasilkan keuntungan karena pengaruhnya terhadap (Romero & Yague, 2016). Oleh karenanya penelitian mengenai keterkaitan brand equity bagi pengambilan keputusan untuk konsumen Shopee perlu menjadi perhatian guna mempertahankan posisi perusahaan dan memberikan gambaran kondisi hubungan antara brand equity dan pengambilan keputusan untuk lokus sektor e-commerce di Indonesia.…”
Section: Sumber : Iprice 2019unclassified
“…For the brand equity, the emerging of brand equity can date back to 1980 [11] , it identified the importance of brand equity which serves as invisible asset that will help a company to gain profits [12] . Asker proposed five essential factors in the model of brand equity, namely brand loyalty, brand awareness, perceived quality, brand associations and other proprietary assets [13] .…”
Section: Brand Equitymentioning
confidence: 99%